Pengembangan Aplikasi Virtual Reality untuk Penyajian Tata Artistik dalam Program Televisi bagi Mahasiswa Program Studi Penyiaran Polimedia - Br Lumban Toruan, Reny Y; Adryans; Ifah Atur Kurniati (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
The utilization of Virtual Reality (VR) technology can be a solution for delivering information in limited online practical learning. Virtual Reality provides a mechanism to change how we view events around us by simulating an artificial space (Lacrama, 2007). The development of VR technology enables students to understand the shape, function, and workings of VR devices in a real and engaging way. As a vocational higher education institution that focuses on practical training, Polimedia needs to find new methods to ensure that students continue to gain sufficient knowledge. The development of this application follows the ADDIE model and involves second-semester students of the Broadcasting Study Program at Polimedia. This research encompasses three testing stages: comprehension, user response, and user experience.